Characteristics and trends in acceptance and commitment therapy research: A bibliometric analysis - Li, Zhihong; Shang, Wenru; Wang, Caiyun; Yang, Kehu; Guo, Juanmei (Frontiers in Psychology, 2022)
Purpose: As acceptance and commitment therapy (ACT) becomes mainstream and a growing body of literature emerges, it is critical to map the global collaborative network and a quantitative and systematic assessment of ACT, as research on this topic is still lacking. This review aims to provide a comprehensive understanding of the trajectory, key themes, and future prospects in ACT research. Methods: Publications were extracted from the Web of Science Core Collection before 2022. Excel 2019, VOSviewer, and CiteSpace software were used to analyze the characteristics and trends of ACT research. Examples include publications trend analysis, authors’ cooperation network analysis, keywords co-occurrence analysis, and citation burst analysis. Results: A total of 799 articles in 314 journals contributed by 2,862 authors from 958 institutions in 52 countries were identified. The number of publications has increased significantly since 2015. The United States/Utah State University is the most productive country /institution; Karolinska Institute, Utah State University, and King's College of London are the most significant nodes. Twohig M.P., Hayes S.C., and Levin M.E. are the most influential authors. Keyword co-occurrence analysis found the curative mechanisms, using network technology or mobile technology as adjuvant therapy, reducing psychological diseases of cancer patients were potential trends. Conclusions: This review is the first attempt of its kind to systematically examine the knowledge structure and draw an evidence map of ACT research. It deepens the understanding of existing research, gives many operable research directions and suggests to future ACT research.